Does coinciding exercise onset with peak caffeine levels improve cycling performance? - Skinner, T.; Taaffe, D.; Leveritt, M.; Coombes, J.; Jenkins, D. (Journal of Science and Medicine in Sport, 2011)
Introduction: Caffeine`s ability to enhance endurance performance is well documented, however the optimal dose and timing of supplementation remains unclear. The ergogenic effect of caffeine is often assumed to be related to the levels of circulating drug present within the blood. The aim of this study was therefore to determine whether coinciding peak serum caffeine concentration with the onset of exercise would result in further improvements in performance compared with beginning exercise a standard 60 min post-supplementation. Methods: In this randomised, placebo controlled, double-blind crossover study, 14 male trained cyclists and triathletes (age 31±5 yr, body mass 75.4±5.7 kg, VO2max 69.5±6.1 ml/kg·min and peak power output 420±35 W, mean±SD) consumed 6 mg/kg caffeine or a placebo either 1 hour (C1h) prior to completing a 40 km time trial (TT40) in the laboratory or when the start of exercise coincided with individual peak serum caffeine concentrations (Cpeak). Cpeak was determined from a separate `caffeine profiling` session that involved monitoring caffeine concentrations in the blood every 30 min over a 4-hour period. The trials were preceded by a standardised pre-exercise meal (2 g/kg carbohydrates) and subjects were tested for hydration and caffeine abstinence. Venous blood was sampled at baseline, 65 and 20 min prior to exercise and 6 min post-exercise for the measurement of serum caffeine, plasma glucose, catecholamine and blood lactate concentrations. Results: Following caffeine ingestion, peak serum caffeine occurred at 120 min in 12 participants and 150 min in 2 participants. Time to complete TT40 was significantly faster (2%; p=0.002) in C1h compared to placebo. A 1% improvement in performance was noted in Cpeak versus placebo, although this was not statistically significant (p=0.240). Whilst no differences in metabolic markers were found between Cpeak and placebo conditions, significant increases in glucose (p=0.005), norepinephrine and epinephrine (p=0.002) were observed in the C1h trial 6 min post-exercise versus placebo. Discussion: The present study suggests that endurance cycling performance is enhanced when caffeine is ingested one hour prior to exercise. However, no significant improvements in performance were observed when peak serum caffeine concentrations coincided with the onset of exercise. Consequently, it appears that it is the temporal proximity of caffeine supplementation to the commencement of endurance exercise, rather than the achievement of peak serum caffeine concentration, that influences the ergogenic potential of caffeine.